Cognitive correlates of dual tasking costs on the timed up and go test in Parkinson disease. (2022) - Harrie, Ashley; Hampstead, Benjamin M.; Lewis, Cate; Herreshoff, Emily; Kotagal, Vikas
Highlights: Different PD TUG dual tasking impairments have different cognitive correlates. PD visuospatial deficits correlate with dual tasking problems when sitting down. PD dual tasking fall risk may be caused by more than just executive dysfunction. Abstract: Introduction: Dual tasking impairments are an increasingly recognized contributor to falls in Parkinson disease (PD) and may be a promising therapeutic target for PD fall prevention trials. Depending on the context, ambulatory dual tasking difficulties may be caused by different types of neurocognitive impairments. Methods: We performed a cross-sectional analysis of 21 participants with PD. All participants underwent detailed neuropsychological testing that was quantified using normative z-scores. All participants completed the 3-meter timed up and go test (TUG), with and without a dual tasking assignment. Biomechanistic properties of the TUG were quantified using APDM wearable OPAL sensors. We explored correlations between dual tasking cost (DTC) in 1) total TUG duration, 2) Sit-to-stand duration, 3) Stand-to-sit duration, and 4) turn velocity. Results: Impaired total DTC in the TUG correlated inversely with global cognitive performance measured using the Montreal Cognitive Assessment (MoCA) (r = −0.4649, p = 0.0337). Sit-to-stand DTC impairments correlated inversely with processing speed on the WAIS-IV Coding (r = −0.5762, p = 0.0063), semantic fluency (r = −0.5100, p = 0.0182) and learning and memory on the Hopkins Verbal Learning Test-Revised total recall (r = −0.5502, p = 0.0098). Impaired stand-to-sit DTC function corelated inversely with visuospatial cognitive function on the Benton Judgement of Line Orientation (JOLO) test (r = −0.5181, p = 0.0161). Conclusions: The link between dual tasking and fall risk in PD may be caused by cognitive features other than executive dysfunction and may vary based on the ambulatory task in question. These findings shed light on the cognitive contributions to falls in PD.